Systematic Review of Avian Influenza Virus Infection and Outcomes during Pregnancy - Rachael Purcell; Michelle L. Giles; Nigel W. Crawford; Jim Buttery (Emerging Infectious Diseases)
Human cases of avian influenza A(H5N2) and A(H5N1) viruses associated with outbreaks in birds and mammals are increasing globally, raising concerns about the possibility of a future avian influenza pandemic. We conducted a systematic review examining 30 reported cases of avian influenza in pregnant women. We found high mortality rates for mothers (90.0%, 27/30) and their babies (86.7%, 26/30) when women were infected with avian influenza virus during pregnancy. Despite being a high-risk population and having worse health outcomes across multiple pandemics, pregnant women are often excluded from vaccine trials. However, as the risk for a new pandemic increases and human vaccines against avian influenza are developed, early inclusion of pregnant women in clinical trials can inform the risk–benefit analysis for both the mother and their newborn infant. Early inclusion of pregnant women in public health vaccination programs is vital for protecting this high-risk population.